The Influence of E-banking Technology Adoption on Sharia Banking Performance Moderated by Islamic Corporate Governance - Nurlaela, Linda; Nasim, Arim; Andriana, Denny (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
The purpose of this study was to determine the role of Islamic Corporate Governance in this case the characteristics of top management and the characteristics of the Sharia Supervisory Board (DPS) in moderating the effect of e-banking technology adoption on Islamic banking performance. In this study, Islamic banking performance is proxied through financial performance as measured by Return on Assets (ROA) and Operational Performance as measured by Operating Expenses to Operating Income (BOPO). Therefore, the research objects in this study are top management characteristics, Sharia Supervisory Board characteristics, e-banking technology adoption, financial performance and operational performance of Islamic banking. Meanwhile, the research subjects are Islamic commercial banks in Indonesia during the period 2016 to 2020. This study uses a quantitative descriptive approach, so the data analysis technique used is descriptive analysis and moderation regression analysis with the help of SPSS Version 26 software. The results of this study indicate that the adoption of e-banking technology has a significant effect on the financial performance of Islamic banking as measured using ROA and has a significant effect on operational performance as measured using BOPO. In addition, ICG successfully moderates the effect of e-banking technology adoption on Islamic banking performance.